Uganda : Fifth Review Under The Policy Support Instrument And Request For Program Extension: Staff Report; Press Release on the Executive Board Discussion; and Statement by the Executive Director for Uganda. (IMF Staff Country Reports; Country Report ;, 2013)
Uganda has benefited from international reserve accumulation. The fiscal stance is tighter mainly owing to delays in execution of a large hydropower project. A suspension of budget support owing to theft of donor funds has curtailed spending plans and hurt growth prospects. The authorities have acknowledged the damage from corruption and responded to the concerns of development partners. Tight policies have led to the achievement of program targets. Sound macroeconomic policies need to be accompanied by reinforced efforts to fight corruption.